2021
DOI: 10.3389/fnagi.2021.710172
|View full text |Cite
|
Sign up to set email alerts
|

Functional Integrity of Executive Control Network Contributed to Retained Executive Abilities in Mild Cognitive Impairment

Abstract: Background: Mild cognitive impairment (MCI) is considered to be a transitional state between normal aging and Alzheimer's dementia (AD). Recent studies have indicated that executive function (EF) declines during MCI. However, only a limited number of studies have investigated the neural basis of EF deficits in MCI. Herein, we investigate the changes of regional brain spontaneous activity and functional connectivity (FC) of the executive control network (ECN) between high EF and low EF groups.Methods: According… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 66 publications
1
16
0
Order By: Relevance
“…Previous research has reported that compared with the elderly, parahippocampal GMV is positively correlated with EF. It is stronger in the elderly than in young adults [ 61 , 62 , 63 ]. We have not come to the same conclusion in this study, which may be related to lower direct correspondence between the parahippocampal GMV and the EF of college students in early adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has reported that compared with the elderly, parahippocampal GMV is positively correlated with EF. It is stronger in the elderly than in young adults [ 61 , 62 , 63 ]. We have not come to the same conclusion in this study, which may be related to lower direct correspondence between the parahippocampal GMV and the EF of college students in early adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…SFG inhibited behavioral bias between immediate rewards and long-term goals (Diekhof and Gruber, 2010 ). PCG and CG play a key role in the executive control of cognition (Carter et al, 1998 ; Liu et al, 2021 ). Brain changes in IFG, MFG, SFG, PCG and CG contribute to ICD in PD.…”
Section: Discussionmentioning
confidence: 99%
“…This finding may be related to the fact that washing OCD inhibits the activity of core brain areas involved in executive control functions [ 43 ], which affects cognitive functions and enhances the urge to wash. In turn, the left middle frontal gyrus shows increased compensatory activity to maintain normal executive functions [ 44 , 45 ]. Therefore, dysfunction in the middle frontal gyrus may be a feature of washing OCD, and the right middle frontal gyrus in particular has a significant discriminatory value in distinguishing checking OCD from cleaning OCD.…”
Section: Discussionmentioning
confidence: 99%